Peningkatan Hasil Belajar Materi Keliling Bangun Datar Menggunakan Model Problem Based Learning (PBL) di Kelas V SDN 15 Anduring Kota Padang - Okza Zulfa; Melva Zainil (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research is based on the results of field observations, namely the low learning outcomes of students due to the lack of learning activities involving students because the learning process is still centered on the teacher, so that students are still less active in the learning process. The purpose of this study is to describe the improvement in student learning outcomes in learning about the circumference of flat shapes using the Problem Based Learning model in class V of SDN 15 Anduring, Padang City. This type of research is classroom action research (CAR) using qualitative and quantitative approaches. This research was conducted in two cycles, with research procedures consisting of planning, implementation, observation, and reflection. The research data obtained are related to the results Problem Based Learning model learning. Data collection techniques in the form of observation analysis, tests and non-tests. The subjects of this study were class teachers as observers, researchers as practitioners or teachers, and 24 students of class V SDN 15 Anduring, Padang City. The results of the study showed that: First, the cycle I teaching module obtained an average of 60% (C), increasing in cycle II to 90% (SB). Second, the results of the implementation of learning aspects of teachers in cycle I obtained an average of 75% (C), increasing in cycle II to 90% (SB). Third, the results of the implementation of learning aspects of students in cycle I obtained an average of 70% (C), increasing in cycle II to 90% (SB). Thus, it can be concluded that the Problem Based Learning model can improve student learning outcomes in learning the Perimeter of Flat Shapes in class V SDN 15 Anduring, Padang City.